Study on pH change characteristics of coal-water slurry containing potassium permanganate under the action of H2S - Qigen Deng; Chaosi Liu; Mengmeng Yao; Zhecheng Zhang (Desalination and Water Treatment)
Based on the response surface methodology, the pH change characteristics of coal-water slurry containing potassium permanganate (KMnO4) under the action of hydrogen sulfide (H2S) were studied, and the relationship between the factors of coal seam H2S content determination was explored. The effect coal rank, temperature and H2S inflow on the pH change of coal-water slurry was analysed. Through response surface methodology analysis, discovering H2S inflow had a significant effect on pH change of the solution, and the interaction between temperature and H2S inflow had a relatively significant effect on pH change of the solution. The optimal conditions were as follows: 36 mL H2S inflow, 36.5 ℃ temperature and medium rank coal. The conditions which had a significant effect on pH change of the solution, and compared with the experimental verification group, the error was small. Analyzing on influence factors of pH change of coal-water slurry, which provides a reference for the subsequent determination of H2S content.